Integrated Energy System Optimal Operation in Coal District With Hydrogen Heavy Trucks - Yin, Junjie; Wang, Jianhua; You, Jun; Chen, Hong; Shi, Wei (Frontiers in Energy Research, 2021)
The coal industry contributes significantly to the social economy, but the emission of greenhouse gases puts huge pressure on the environment in the process of mining, transportation, and power generation. In the integrated energy system (IES), the current research about the power-to-gas (P2G) technology mainly focuses on the injection of hydrogen generated from renewable energy electrolyzed water into natural gas pipelines, which may cause hydrogen embrittlement of the pipeline and cannot be repaired. In this paper, sufficient hydrogen energy can be produced through P2G technology and coal-to-hydrogen (C2H) of coal gasification, considering the typical scenario of coal district is rich in coal and renewable energy. In order to transport the mined coal to the destination, hydrogen heavy trucks have a broad space for development, which can absorb hydrogen energy in time and avoid potentially dangerous hydrogen injection into pipelines and relatively expensive hydrogen storage. An optimized scheduling model of electric-gas IES is proposed based on second-order cone programming (SOCP). In the model proposed above, the closed industrial loop (including coal mining, hydrogen production, truck transportation of coal, and integrated energy systems) has been innovatively studied, to consume renewable energy and coordinate multi-energy. Finally, an electric-gas IES study case constructed by IEEE 30-node power system and Belgium 24-node natural gas network was used to analyze. The results show that by introducing the proposed hydrogen production technology, typical daily operating costs are effectively reduced by 7.7%. Under China's carbon emissions trading system, the operating costs of hydrogen heavy trucks have been reduced by 0.95% and 4.68% respectively, compared with electric vehicles and diesel trucks. Under Europe's stricter carbon emissions trading system, the percentages of cost reduction are 2.56% and 9.12%, respectively. The above technical results verify the feasibility, economy, low carbon, and effectiveness of the proposed mechanism.